8 Channel MIMO Long Range Radar Concept for Angular Estimation in Multi Target Scenarios - Lutz, Steffen; Erhart, Christian; Walter, Thomas; Weigel, Robert (IEEE MTT-S International Conference on Microwaves for Intelligent Mobility (ICMIM), 2015)
In this contribution a novel concept for a lens based 8 channel MIMO radar is presented. Hereby the sensor concept deals with a combination of optical beamforming based on a dielectric lens and the classical MIMO radar approach to increase the angular resolution. The sensor architecture is presented, the antenna concept introduced and characterized by measurements. After a brief formulation of the signal model, the evaluation of the angular performance based on the Cramer-Rao lower bound is introduced. The paper concludes with the comparison between MIMO and MISO radar processing in real world multiple target scenarios.
elib2cris::1512001600,lutz2015